Case Report: A homozygous mutation in the SPAG17 gene in a case with oligoasthenoteratozoospermic infertility - Sethi, Shruti; Andrabi, Waseem; Mitra, Kalyan; Rajender, Singh (Frontiers in Reproductive Health, 2025)
BackgroundDefects in sperm size and form, known as teratozoospermia, can adversely impair sperm motility and its ability to fertilize an oocyte. Teratozoospermia has been most often linked with genetic abnormalities with close to 100 genes known.ObjectiveThe primary objective of this study was to investigate the genetic basis of oligoasthenoteratozoospermic infertility in an infertile man.MethodsWe performed the whole exome sequencing, followed by in silico filtration of observed genetic variations. Filtered rare variants were assessed for their pathogenic nature on the basis of scores assigned by various in-silico tools and their biological relevance to sperm structural development. The potential pathogenic mutation was validated by Sanger sequencing.ResultsOur study identified a homozygous substitution, c.4511A > G, in the SPAG17 gene as a potential pathogenic mutation associated with oligoasthenoteratozoospermic infertility in the case under investigation. The mutation resulted in the substitution of asparagine with serine at the 1504th amino acid position in a protein of 2,223 amino acids. This mutation shows a minor allele frequency of 0.0004671 in the gnomAD database. ACMG classification suggested this mutation to be likely pathogenic.ConclusionOur study identified a homozygous likely pathogenic mutation (c.4511A > G, Asn1504Ser) in the SPAG17 gene that explains oligoasthenoteratozoospermic infertility in the present case.